STUDY ANALYSIS OF THE IMPLEMENTATION OF THE JOINT DECREE OF FOUR MINISTERS ON LIMITED FACE-TO-FACE LIMITED IMPLICATIONS ON PAI LEARNING IN SMA REGENCY OF PEMALANG - IKA PURWANTI (Proceeding Of The International Seminar and Conference on Global Issues, 2020)
ABSTRACTLearning in the world education is a process of interaction that occurs between teachers and students either directly, such as face-to-face activities (offline) or indirectly (online), by using media, models and learning methods. Countries in the world are currently facing the Covid-19 pandemic, including Indonesia. The Covid-19 pandemic has become a major human crisis, because humans are forced to stop from the routine of their daily lives and are asked to stay at home. The spread of the corona virus in various countries has mademajor changes, such as the economy, technology, and education is no exception. In the realm of education, to overcome this problem, the government announced a Joint Decree (SKB) of the Minister of Education and Culture, the Minister of Religion (Menag), the Minister of Health (Menkes), and the Minister of Home Affairs (Mendagri) regarding Guidelines for the Implementation of Learning in Even Semesters of the Academic Year and Academic Year2020/2021 during the Covid-19 Pandemic. This type of research uses qualitative methods. So that this approach is a research procedure that produces descriptive data in the form of written and spoken words from people with observable behavior and is directed at natural and individual settings as a whole. The purpose of the field research carried out was to study the reasons behind the issuance of a Joint Decree of the Four Ministers concerning Limited Face- to-Face Learning in improving the Learning Process of Islamic Religious Education Materials in Pemalang District High Schools, to find out how to implement the Joint Decree of the Four Ministers concerning Limited Face-to-Face and its Implications for Learning. Islamic Religious Education in Senior High Schools in Pemalang Regency and the impact or influence of the implementation of the Joint Decree of the Four Ministers concerning Limited Face-to-face Meetings. Keywords : learning, implementation, religious education